Preparing Indonesia’s Future Governance Leaders: Reviewing New Horizons for Public Administration Education - Muluk, Mujibur Rahman Khairul; Sajida, Sajida (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
This research examines the future trajectories of public administration science in Indonesia, considering the evolving demands of governance and problems in pedagogy. This analysis is primarily based on an extensive literature review that examines how various trends from both global and national contexts, including digitalization, interdisciplinary shifts, and value pluralism, influence curricula, leadership preparation, and research expectations. Identified are enduring deficiencies in institutional capacity, advancements in teaching, and methodological diversity. The report asserts that public administration education requires reconfiguration to transcend bureaucratic training and focus on ethical leadership, systems thinking, and local governance literacy. The document serves as a conceptual instrument for realigning public administration initiatives to the evolving difficulties of governance and preparing a new cohort of public leaders for dynamic, value-driven, and adaptive public service.